HEALTH EDUCATION THROUGH VIDEO MEDIA IMPROVES THE KNOWLEDGE AND ATTITUDE OF PERSONAL HYGIENE IN PREVENTING LEUCORRHOEA IN ADOLESCENT GIRLS - Syaiful, Yuanita; Fatmawati, Lilis; Adawiyah, Robiatul (SYNTIFIC, 2023)
Background. Lack of knowledge and attitudes about personal hygiene in preventing leucorrhoea in adolescent girls’ is due to a lack of health promotion, one that can increase knowledge and attitudes about personal hygiene is health education with videos. The purpose of this community service was to 1) increase adolescent girls’ nowledge about personal hygiene in preventing leucorrhoea, and 2) improve adolescent girls’ attitudes about personal hygiene in preventing leucorrhoea. Implementation Method. This community service was carried out for adolescent girls’ aged 16-18 years in Yosowilangun Manyar Gresik Village with a total of 16 adolescent girls’. The activity was carried out on May 20-27, 2022. The method used was in the form of providing health education about personal hygiene in preventing vaginal discharge with video media using a pre-test and post-test. Findings. The results of the activity showed that the majority of 14 adolescent girls’ (87.5%) had good knowledge and the majority had a positive attitude, namely 15 adolescent girls’ (93.75%) Conclusion. Health education with video media can increase knowledge skills and personal hygiene attitudes in adolescent girls’ in preventing leucorrhoea.